2021
DOI: 10.1038/s41379-021-00825-7
|View full text |Cite
|
Sign up to set email alerts
|

Counting mitoses: SI(ze) matters!

Abstract: Mitoses are often assessed by pathologists to assist the diagnosis of cancer, and to grade malignancy, informing prognosis. Historically, this has been done by expressing the number of mitoses per n high power fields (HPFs), ignoring the fact that microscope fields may differ substantially, even at the same high power (×400) magnification. Despite a requirement to define HPF size in scientific papers, many authors fail to address this issue adequately. The problem is compounded by the switch to digital patholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(58 citation statements)
references
References 33 publications
(48 reference statements)
0
38
0
1
Order By: Relevance
“…Poor reproducibility may result from various causes, including sampling (complete lymph node excision versus core needle biopsy), definition and recognition of centroblasts, and methods of enumeration. Since grading of FL is based on the enumeration of centroblasts per high-power field (HPF), one of the challenges is the lack of a consistent definition of a HPF using a 40x microscope objective (400x magnification), where the size of the microscopic field has changed over the years even at the same magnification [ 94 ]. Lack of consensus regarding the morphological spectrum of centroblasts and using conventional methods of counting further negatively impacts reproducibility [ 95 ].…”
Section: B-cell Lymphoid Proliferations and Lymphomasmentioning
confidence: 99%
“…Poor reproducibility may result from various causes, including sampling (complete lymph node excision versus core needle biopsy), definition and recognition of centroblasts, and methods of enumeration. Since grading of FL is based on the enumeration of centroblasts per high-power field (HPF), one of the challenges is the lack of a consistent definition of a HPF using a 40x microscope objective (400x magnification), where the size of the microscopic field has changed over the years even at the same magnification [ 94 ]. Lack of consensus regarding the morphological spectrum of centroblasts and using conventional methods of counting further negatively impacts reproducibility [ 95 ].…”
Section: B-cell Lymphoid Proliferations and Lymphomasmentioning
confidence: 99%
“…30 ). Pathologists should document the methodology used in their assessment of Ki67 and mitotic count [ 171 ].
Fig.
…”
Section: Question 9: What Is the Role Of Mitotic Tumor Grade And The ...mentioning
confidence: 99%
“…For example, in 2017 the cut-off was clarified such that cases with an index less than 3.0 (including 2.99), which were previously unclear as to which grade this belonged, now clearly included Grade 1 9 . Naturally, as in any grading and staging system that assesses a continuous variable, the Ki-67 index-based system is imperfect 54 . For example, it can be expected that cases with 2.99 (now in G1) and 3.0 (now in G2) will be similar in biological behavior.…”
Section: Discussionmentioning
confidence: 99%
“…In this review, we chose to focus on PanNENs. However, the topic of manual vs. digital pathology scoring of Ki-67 is also certainly of importance for NENs at many other anatomic sites 54 , as well as for other neoplasms in which DIA-based systems are being leveraged to assess biomarkers. In 2015, Joseph et al studying a cohort of 48 lung carcinoids, demonstrated an overall similarity of manual counting vs. DIA; although Ki-67 estimation resulted in slightly higher results than manual counting 59 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation